2008
DOI: 10.1111/j.1567-1364.2008.00445.x
|View full text |Cite
|
Sign up to set email alerts
|

Human p53 induces cell death and downregulates thioredoxin expression inSaccharomyces cerevisiae

Abstract: The p53 tumour suppressor protein has a crucial role in controlling cell cycle and apoptosis in human cells and its inactivation by selective point mutations is associated with human cancers. Here we show that overexpression of the human wild-type (wt) p53 in Saccharomyces cerevisiae completely inhibits yeast growth under minimal media conditions. In contrast, the R248W 'hot spot' p53 mutant (one of the most frequent p53 mutations encountered in human cancers) does not impair yeast growth. Moreover, we report,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 30 publications
(46 reference statements)
4
38
0
Order By: Relevance
“…Previously, it has been demonstrated that overexpression of p53 in yeast growing on minimal medium causes growth retardation, presumably due to an apoptotic pathway triggered by functional p53 (21). We used this phenotype to assess the loss of function of p53 in cells harboring seeds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been demonstrated that overexpression of p53 in yeast growing on minimal medium causes growth retardation, presumably due to an apoptotic pathway triggered by functional p53 (21). We used this phenotype to assess the loss of function of p53 in cells harboring seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, there was no difference between the supernatant and pellet fractions of the cells with and without seeds, which was starkly different for p53. The detergent insolubility property of the amyloids has been used to isolate amyloid-containing fractions from yeast cell lysate by centrifugation (21,22). We sought to use this detergent insolubility property to demonstrate the amyloidogenic characteristics of the p53 aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the basal machinery of the apoptotic process is evolutionary conserved, because in yeast we can observe all phenotypic markers of apoptosis such as chromatin condensation, mitochondria fragmentation, and cytochrome c release. In particular, S. cerevisiae has been successfully used to study the regulation of apoptosis by either WT or mutated p53 (35). More recent data also revealed the conservation in yeast of functional transcription-independent p53 apoptotic functions and p53-induced mitochondria fragmentation (29,36).…”
Section: Volume 286 • Number 46 • November 18 2011mentioning
confidence: 99%
“…These early studies seem to have uncovered a bona fide effect of p53 because a recent study has reported that p53 regulates cell cycle progression in mammalian cells by interacting with cdc25. 76 Although it is quite clear that there is no direct orthologue of p53 in the yeast genomes, these and various other studies 77 suggest that a functional homologue to p53 is likely to exist in yeast. Although alternative explanations exist, the ability of these heterologous human apoptotic regulators to function in yeast is largely taken as evidence for the underlying similarities in the regulation of apoptosis in yeast and mammalian cells.…”
Section: Analysis Of Tumour Suppressors In Yeastmentioning
confidence: 94%
“…Observations in mammalian cells also support this later idea, as previous studies have made associations between alterations in Trx expression in tumours in general, as well as in tumours with mutant p53 genes. 77 Earlier studies had noticed a link between oxidative stress and p53 function in yeast. 78 It was reported that there was loss of the transcriptional factor activity of p53 in yeast strains lacking the thioredoxin reductase 1 (TRR1) gene.…”
Section: Analysis Of Tumour Suppressors In Yeastmentioning
confidence: 99%